2012
DOI: 10.1093/icvts/ivs295
|View full text |Cite
|
Sign up to set email alerts
|

Does muscle-sparing thoracotomy as opposed to posterolateral thoracotomy result in better recovery?

Abstract: A best evidence topic was written according to a structured protocol. The question addressed was whether muscle-sparing thoracotomy (MST), as opposed to posterolateral thoracotomy (PLT), results in better recovery. A total of 108 papers were found using the reported searches of which eight represented the best evidence to answer the clinical question. The authors, date, journal, study type, population, main outcome measures and results are tabulated. A recent large prospective, randomized, double-blinded, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Patients want information about HRQoL outcomes after cancer surgery, but surgeons rarely inform the patients about such outcomes. Trauma related to thoracotomy is associated with postoperative pain. Pain and decreased exertion caused by open surgery may have a strong influence on respiratory function, pulmonary complication rate and postoperative HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Patients want information about HRQoL outcomes after cancer surgery, but surgeons rarely inform the patients about such outcomes. Trauma related to thoracotomy is associated with postoperative pain. Pain and decreased exertion caused by open surgery may have a strong influence on respiratory function, pulmonary complication rate and postoperative HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that up to 50 % of patients describe post-thoracotomy pain 1 year after the procedure [ 23 ]. A recent study on the type of thoracotomy found an inverse relationship between the incision length and post-thoracotomy pain [ 24 ]. With MIE both incision length and myofascial damage is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, Jiwnani's paper is not the first study comparing PLT versus NST. In 2014 Celikten (7) and co-workers presented a similar study with consistent conclusions and, in 2012, Elshiekh et al (8), presented a best evidence topic set as a protocol as reported in IVCTS (9). Conclusions were based on a selection of prospective randomized studies and suggested that MST better preserve muscle strength and arm motion but only in the first postoperative week.…”
Section: Nst a Further Innovationmentioning
confidence: 86%